The Future of Work in the Financial Service Industry Post COVID-19: A Case of Costa Rica (Global Journal of Management and Business Research, 2022)
The health crisis caused by COVID-19 transformed the operational paradigm of financial industry in Costa Rica. The context demanded high levels of resilience and innovation to face the effects of the pandemic. Therefore, the general objective of this research is to describe the main variables that characterize the future of work in the Costa Rican financial service industry in a post-COVID-19 scenario.
Keywords: remote work; future of work; financial industry; automation